Sharing information about domestic violence and abuse in healthcare: an analysis of English guidance and recommendations for good practice - Gene Feder; Sandi Dheensa (BMJ Open)
Background Over two million adults experience domestic violence and abuse (DVA) in England and Wales each year. Domestic homicide reviews often show that health services have frequent contact with victims and perpetrators, but healthcare professionals (HCPs) do not share information related to DVA across healthcare settings and with other agencies or services.Aim We aimed to analyse and highlight the commonalities, inconsistencies, gaps and ambiguities in English guidance for HCPs around medical confidentiality, information sharing or DVA specifically.Setting The English National Health Service.Design and method We conducted a desk-based review, adopting the READ approach to document analysis. This approach is a method of qualitative health policy research and involves four steps for gathering, and extracting information from, documents. Its four steps are: (1) Ready your materials, (2) Extract data, (3) Analyse data and (4) Distill your findings. Documents were identified by searching websites of national bodies in England that guide and regulate clinical practice and by backwards citation-searching documents we identified initially.Results We found 13 documents that guide practice. The documents provided guidance on (1) sharing information without consent, (2) sharing with or for multiagency risk assessment conferences (MARACs), (3) sharing for formal safeguarding and (4) sharing within the health service. Key findings were that guidance documents for HCPs emphasise that sharing information without consent can happen in only exceptional circumstances; documents are inconsistent, contradictory and ambiguous; and none of the documents, except one safeguarding guide, mention how coercive control can influence patients’ free decisions.Conclusions Guidance for HCPs on sharing information about DVA is numerous, inconsistent, ambiguous and lacking in detail, highlighting a need for coherent recommendations for cross-speciality clinical practice. Recommendations should reflect an understanding of the manifestations, dynamics and effects of DVA, particularly coercive control.